Highly efficient and selective CO2-adjunctive dehydration of xylose to furfural in aqueous media with THF. Issue 8 (10th February 2016) - Morais, Ana Rita C.; Bogel-Lukasik, Rafal
Abstract : The selective dehydration of xylose into furfural using high-pressure CO2 as an effective and more sustainable catalyst in an H2 O/THF system is reported for the first time. Abstract : The selective dehydration of xylose into furfural using high-pressure CO2 as an effective and more sustainable catalyst in an H2 O/THF system is reported for the first time. The conversion ofd -xylose into furfural above 83 mol% with a furfural yield of 70 mol% and a selectivity of 84% was achieved with only 50 bar of CO2 pressure within 1 hour at 180 °C.